LEVERAGING TECHNOLOGY AND AI FOR PERSONALIZED LISTENING PRACTICE IN ENGLISH LANGUAGE TEACHING - Zubaydova Nilufar Neʼmatullayevna; Umurzakova Raykhona (TADQIQOTLAR.UZ, 2024)
Annotation: This article explores the potential of artificial intelligence (AI) and technology in personalizing listening practice for English language learners. By examining AI-driven tools, such as speech recognition applications and virtual teaching assistants, the study highlights how these technologies can customize listening exercises to meet each learner’s proficiency level and specific needs. The article discusses the benefits of adaptive learning technologies, such as providing real-time feedback, addressing unique linguistic challenges, and enhancing engagement through tailored content. This analysis offers insights into how technology-enabled, individualized instruction can improve listening comprehension skills and foster a more effective, student-centered approach to teaching English.